Remdesivir Use in Pediatric Patients with Acute SARS-CoV-2 Infection Is Safe and Well Tolerated - Delma J. Nieves; M. Tuan Tran; Jasjit Singh; Negar Ashouri; Tricia Morphew; Jennifer G. Lusk; Felice C. Adler-Shohet; Rachel Marano; Stephanie Osborne; Jennifer Strickland; Antonio C. Arrieta (Children)
Background/Objective: Millions of children were infected with SARS-CoV-2, and a small proportion progressed to severe disease, especially those with underlying risk factors. Adult COVID-19 studies showed mortality benefits with Remdesivir. Data on Remdesivir use in pediatrics are limited. We report on the safety and tolerability of Remdesivir in pediatric patients seen at our institution. Methods: This was a retrospective cohort study of patients <19 years old with acute SARS-CoV-2 infection who received at least one dose of Remdesivir. Patients followed strict institutional guidelines for safety monitoring including standard clinical and laboratory daily observations. Demographics and underlying conditions were reported as averages; for laboratory values, linear regression was applied within a generalized linear mixed-effects model framework to evaluate the significance of changes in average levels over time. Results: We enrolled 318 patients with acute SARS-CoV2 infection from May 2020 to December 2022. In total, 53% were male, and the age range was distributed broadly. In total, 61% were school-aged children (28% 5–11 and 33% 12–18 years of age). In total, 62% of cases were Hispanic. The most common reasons for Remdesivir treatment included respiratory distress (201; 63%) and having high-risk underlying conditions (109; 34%). Therapy was completed as planned in 91% and discontinued early in 9%. Mean baseline, peak, and end of treatment values for AST were 57 (95% CI 53, 61), 79 (95% CI 73, 84) (p < 0.001), and 55 (51, 59) (p = 0.479); for ALT, they were 42 (38, 47), 59 (95% CI 52, 66) (p < 0.001), and 46 (95% CI 41, 52) (p = 0.054); and for bilirubin, they were 0.56 (95% CI 0.50, 0.62), 0.67 (95% CI 0.61, 0.74) (p < 0.001), and 0.44 (95% CI 0.40, 0.48) (p < 0.001), respectively. During Remdesivir treatment, we did not observe marrow suppression or renal toxicity. Conclusions: No clinically significant hematological or renal toxicity was noted. Mean liver enzymes increased modestly and returned to baseline without interrupting treatment. Remdesivir was well tolerated in patients <19 years old.